Towards Useful Social Capabilities for Robots in Healthcare - Merz, Nina; Wittenberg, Thomas; Klein, Stina; Lu, Shuang; Zebisch, Raoul; Retzer, Lukas; Niessen, Cornelia; Kraus, Matthias; Andre, Elisabeth; Lang-Richter, Nadine; Pest, Christian; Berger, Julia; et al. (2024 2nd International Conference on Integrated Systems in Medical Technologies (ISMT), 2024)
Social robots aim to solve existing challenges in healthcare and nursing. Nevertheless, such robots are not yet capable of robustly engaging in a diverse range of social interactions. Furthermore, the development of such robots and their adaptation to new healthcare scenarios is both time-consuming and cost intensive. Resulting in only pilot studies in some exemplary healthcare scenarios. This contribution presents the Concept for Enabling Robots for Useful Social Interactions in Healthcare (CERUSI-Health) - including requirements, software architecture, social situative communication and socially adaptive and proactive interaction for social robots and simulation and validation and impacts of social robots. The objective of CERUSI-Health is to overcome existing obstacles to the use of social robots as assistants in the healthcare and nursing sector. The concept is based on the current state of research and thus including open research gaps, but provides guidance on how these can be addressed. Given the variety of tasks in the healthcare and nursing sector, it is possible to enable different kinds of robots to act socially by following CERUSI-Healt